The effect of time, temperature and solid to solvent ratio on pumpkin carotenoids extracted using food grade solvents - Norshazila S.,; Koy, C.N.; Rashidi O.,; Ho, L.H.; Azrina I,; Nurul Zaizuliana R.A.,; Zarinah Z., (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study aimed to extract carotenoids from pumpkin (Cucurbita moschata) by using food grade solvents (ethanol, ethyl acetate, acetic acid and virgin coconut oil). The influence of different extraction conditions; temperature of extraction (15, 30 and 45℃), duration of extraction (12, 18 and 24 h) and solid to solvent ratio (1:50, 1:100 and 1:150) on yield of carotenoids were also evaluated for optimization purposes. The compounds of the extracted carotenoids were identified by using high performance liquid chromatography (HPLC). The detected carotenoids from pumpkin had been α-carotene, β-carotene and lutein. Lutein was found to have the highest concentration in pumpkin. Furthermore, the results obtained from the yield of carotenoids showed that sample extracted with ethyl acetate was insignificant and this differed from that with virgin coconut oil extract (77.30 and 76.64 β-carotene μg/g dry matter, respectively). Meanwhile, the samples extracted by using either acetic acid or ethanol had presented low yields (68.10 and 54.98 β-carotene μg/g dry matter, respectively). Nevertheless, the extract of carotenoids was found to be optimized at the following extraction conditions; 1:150 solid to solvent ratio and extracted by using virgin coconut oil for 12 h at 30oC.